Design and Development of a Transparency Information Website on the Use of Village Funds in Durian IV Mbelang Village - Crisna Imanuel Tarigan; Hadi Kurnia Saputra; Lativa Mursyida; Delvi Asmara; sinaga, lotar mateus (Cattleya Darmaya Fortuna, 2024)
This study focuses on developing a website for transparency in the use of Village Funds in Durian IV Mbelang Village, so that the community can more easily monitor the allocation and utilization of village funds. The main problem was the limited access to information related to village funds which hinders community participation in supervision. The proposed solution included developing a website using the Waterfall method and the Laravel framework, equipped with PHP technology for coding and MySQL for data management, with the aim of providing easy access and transparency of information for village communities. The development process started from analyzing user needs to implementing features for information accessibility. Testing using the Black Box method and User Acceptance Testing (UAT) showed that this website is effective in providing real-time information and can be easily accessed. Overall, this website is expected to be able to increase community involvement in monitoring the use of Village Funds and strengthen the accountability of its management.